Carl Milles: Master of Fountains An Interview With Kent Ullberg. Issue 3 (September 2019) - Alt, Gordon
This past June, I had the opportunity to participate in the National Sculpture Society Annual Meeting in Brookgreen Gardens, and attended a fountain-side talk on Carl Milles' Fountain of the Muses. It was given by Swedish/American naturalist and sculptor Kent Ullberg FNSS. After returning to Washington, I decided to revisit Milles' Fountain of Faith just outside Washington. I realized after seeing these two important fountains, which were Milles' last two major installations, that it would be an important opportunity to interview Kent on his personal insights and experience with Milles' work, as well as the influence Milles had on his own growth as a sculptor. It is also an opportunity to reflect how important this giant of fountain design was to public art in this country and how much influence he still has on fountain design.